Men and Bodybuilding: A study of health work, masculinity, and bodybuilding - Bailey, Brian James (My University, 2021)
This dissertation is the product of ethnographic and participant observation research into the social worlds of men that pursue the achievement of health through their participation in bodybuilding and consumption of sports nutrition supplements. Theoretical and empirical literature on the sociology of health, gender and aging, bodybuilding, social constructionism, phenomenology, and social reproduction are leveraged to frame and interpret the narratives shared by men participating in this research. In total, 32 digitally recorded interviews were conducted with male bodybuilders between the ages of 18 and 68 who were living a seemingly heteronormative lifestyle. They took place between September 2007 and June 2008 most often in local coffee shops or in participants’ homes; five interviews were conducted over the telephone. The interviews lasted an average of 52 minutes. While men participating in this study identified, in some way, with being a bodybuilder, only a few provincial or national level competition winners identified as being ‘hardcore’. In three substantive chapters, I address: (1) how men engage in health work and masculine identity construction through bodybuilding at various stages of the life course, (2) which sources of knowledge they consult and trust to learn about bodybuilding activities (e.g. weight training techniques, dieting strategies, sports nutrition supplement consumption practices), and (3) how, for a subset of participants, they develop and exchange cultural capital for economic capital through employment in bodybuilding industries. Collectively, this research has contributed to our understanding of the intersection between male bodybuilding, health, and masculinity.
Keywords: masculinity; bodybuilding; health; identity construction; sports nutrition supplements; life course; sociology